Motives and preferences of general practitioners for new collaboration models with medical specialists: a qualitative study - Berendsen, Annette J (BioMed Central, 2007)
BACKGROUND: Collaboration between general practitioners (GPs) and specialists has been the focus of many collaborative care projects during the past decade. Unfortunately, quite a number of these projects failed. This raises the question of what motivates GPs to initiate and continue participating with medical specialists in new collaborative care models. The following two questions are addressed in this study: What motivates GPs to initiate and sustain new models for collaborating with medical specialists? What kind of new collaboration models do GPs suggest? METHODS: A qualitative study design was used. Starting in 2003 and finishing in 2005, we conducted semi-structured interviews with a purposive sample of 21 Dutch GPs. The sampling criteria were age, gender, type of practice, and practice site. The interviews were recorded, fully transcribed, and analysed by two researchers working independently. The resulting motivational factors and preferences were grouped into categories. RESULTS: 'Developing personal relationships' and 'gaining mutual respect' appeared to dominate when the motivational factors were considered. Besides developing personal relationships with specialists, the GPs were also interested in familiarizing specialists with the competencies attached to the profession of family medicine. Additionally, they were eager to increase their medical knowledge to the benefit of their patients. The GPs stated a variety of preferences with respect to the design of new models of collaboration. CONCLUSION: Developing personal relationships with specialists appeared to be one of the dominant motives for increased collaboration. Once the relationships have been formed, an informal network with occasional professional contact seemed sufficient. Although GPs are interested in increasing their knowledge, once they have reached a certain level of expertise, they shift their focus to another specialty. The preferences for new collaboration models are diverse. A possible explanation for the differences in the preferences is that professionals are more knowledge driven than organisation driven as the acquiring of new knowledge is considered more important than the route by which this is achieved. A new collaboration model seems a way to acquire knowledge. Once this is achieved the importance of a model possibly diminishes, whereas the professional relationships last.